XRS MOTOR - CENTRO PORSCHE PORTO - Teixeira, Mariana (My University, 2024)
Este presente relatório, no âmbito do Mestrado em direção comercial e marketing realizado no ISAG – Instituto superior de administração e gestão, tem como primeiro e principal objetivo descrever as tarefas que foram desenvolvidas ao longo de todo o período de estágio curricular no Centro Porsche Porto, sob a orientação de Catarina Marques. Numa primeira fase, é realizado um panorama geral do mercado automóvel português, passando de seguida ao diagnóstico da empresa, onde são apresentados todos os dados relevantes para que a análise seja feita de forma completa, abrangendo análise interna e externa. Numa parte final, de forma bastante simples, são apresentados os resultados de um inquérito que foi realizado para avaliação do evento anual da empresa de forma a avaliar a satisfação dos colaboradores. Durante todo o processo, fui algumas vezes desafiada com tarefas que saiam da minha zona de conforto naquilo que é considerada a minha experiência de trabalho o que, por vezes, se podia tornar difícil sendo que este

This report, within the scope of the master’s degree in Commercial Management and Marketing at ISAG - Instituto Superior de Administração e Gestão, has as its first and main objective to describe the tasks that were carried out throughout the internship period at the Porsche Porto Center, under the guidance of Catarina Marques. In the first phase, a general overview of the Portuguese automobile market is given, followed by a diagnosis of the company, where all the relevant data is presented so that the analysis can be carried out in a complete way, covering both internal and external analysis. In the final part, the results of a survey that was carried out to evaluate the company's annual event to assess employee satisfaction are presented in a very simple way. Throughout the process, I was sometimes challenged with tasks that went outside my comfort zone in what is considered my work experience, which could sometimes be difficult given that this was an unknown market and one with which I had no experience whatsoever. The consumer and their experience are one of the key points for the company and the brand, so it's extremely important that everything is geared towards them. From the decor to the service provided by the employees. That's what the brand's strategy is all about, trying to give the consumer what they want and what will satisfy their ego, since the brand lives off that and that experience as the owner of a luxury item.
Keywords: Consumidor; Experiência; Estratégia de marca; Identidade social; Luxo